Auditoría de la seguridad informática del centro de cómputo de la M. I. Municipalidad del cantón Pasaje aplicando la norma de ISACA - Cordero Sánchez, Fanny Ivonne (2010)
In this research work we have audited the Department of Computer Systems the M. I. Municipality of the Canton Pasaje, applying the rule of association Audit and Control Information Systems ISACA, meeting standards, guidelines and procedures that provide for audits and following the proposed methodology.